Analisis Pelaksanaan Pembiayaan Ijarah Multijasa untuk Re- planting Kebun Kelapa Sawit menurut Fatwa Dewan Syariah Nasional (Studi Kasus Di Pt.Bank Muamalat Indonesia Tbk. Kantor Cabang Padang) - Lubis, Riyani Fitri (Jurnal AL-AHKAM, 2019)
Shariah banking operations have ignored the absurdity of applying the principles in the contract . In practice there is also a discrepancy between its practice and Islamic law. Shariah banking provides technical funding that is  considered only relatively easier  to  implement. At PT. Bank  Muamalat Indonesia  Tbk. Branch  Office of  Padang, for  multi-service  financing used contract ijarah. While  in  the  financing is required package services  and re- planting goods.  The focus of these studied research is implementation mul- tijasa ijarah financing for replanting of   oil   palm   plantations at   PT . Bank Muamalat Indonesia Tbk. Padang Branch Office has been according accord- ingly Fatwa of Sharia National Council . The purpose of this study is to analyze and disclose the review Fatwa of Sharia National Council on the implemen- tation  of multijasa ijarah financing for replanting of  oil  palm  plantations in PT. Bank Muamalat Indonesia Tbk. Branch Office of Padang. This research is in the form of qualitative deskriptif. The results of this study show that im- plementation of multijasa ijarah financing at PT. Bank Muamalat Indonesia Tbk. The Branch Offices of Padang for replanting the oil palm plantations as a whole have not been in accordance with the Fatwa of Sharia National Council. As for things that are not in accordance with the Fatwa of Sharia Na- tional Council is the writing of ujrah.  Ujrah at PT. Bank Muamalat Indonesia Tbk. Branch Office of Padang is still written in the percentage of 14% of year, although it is from the agreement between both parties, but in the Fatwa of Sharia National Council  Board fatwa on multijasa ujrah financing not in per- centage form but in nominal form.